VARIETIES OF BAQLAJON WITH VALUABLE FARM CHARACTERISTICS - Turayev Dilshod Shodavlatovich; Aramov Muzaffar Xoshimovich Sabzavot (Web of Journals Publishing, 2024)
The article presents the results obtained at the Surkhandarya Scientific Experimental Station of the Institute of Vegetable Growing, Melon Crops and Potato Growing in 2021-2023 on early-ripening, nematode-resistant varieties and lines of eggplant. The study showed that the highest total yield was observed in the TRIAL sample brimdal 972 variety and was 35.3% higher than in the standard variety, with a yield of 82.1 t/ha.
Keywords: eggplant, root knot nematodes, selection, line, stability, grade, standard grade, early maturity, productivity.